Amnesty international Indonesia’s strategy for mainstreaming human rights in the 2024 presidential election campaign - Jessica Erviranda Ningtyas; Havidz Ageng Prakoso; Shannaz Mutiara Deniar (Universitas Islam Malang, 2026)
The 2024 Indonesian Presidential Election exposed persistent tensions between human rights advocacy and state power amid shrinking civic space and weakened state responsiveness to accountability demands. Within Transnational Advocacy Network (TAN) scholarship, this context highlights an unresolved theoretical problem, namely the assumption that symbolic mobilization and transnational pressure necessarily generate substantive policy change. This assumption becomes problematic when advocacy achieves high visibility without meaningful state response, a limitation that remains underexamined in studies of symbol based advocacy and public participation. This article analyzes how the core instruments of TAN information politics, symbolic politics, leverage politics, and accountability politics are operationalized in Amnesty International Indonesia’s #ALLOUT campaign in the post election period. Employing a qualitative approach, the study examines campaign documentation, organizational archives, and public advocacy materials, complemented by in depth interviews with Amnesty International Indonesia’s National Campaign Coordinator and a representative of KontraS. The unit of analysis centers on the operationalization of TAN instruments in post election advocacy. The findings indicate that #ALLOUT operates through a symbolic declarative logic rather than escalating political pressure, prioritizing the maintenance of narratives, public memory, and normative claims. In this context, accountability politics functions primarily as a defensive mechanism to sustain human rights discourse rather than to induce direct policy change. This study contributes to TAN scholarship by reframing advocacy outcomes as the preservation of discursive space and normative continuity within restrictive political settings.